My one-of-a-kind body : the ultimate guide to caring for me - Casares, Whitney (American Academy of Pediatrics, 2026)
Everybody has a body, and if you take care of it -- even if it is weird -- it will take you all kinds of places and help you do all kinds of things! Get tips on feeding, moving, and enjoying your body, but most of all being nice to it and yourself.